2004
DOI: 10.1016/j.ejpain.2004.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of coeliac plexus and splanchnic nerve blockades in body and tail located pancreatic cancer pain

Abstract: Palliative treatment, pain therapy and quality of life (QOL) are very important in pancreatic cancer patients. We evaluated the pain relieving efficacy, side effects and effects on QOL of neurolytic coeliac plexus blockade (NCPB) and splanchnic nerves neurolytic blockade (SNB) in body and tail located pancreatic cancer. The study protocol was approved by the local ethics committee. Patients were randomly divided into two groups. Coeliac group; GC, N = 19 were treated with coeliac plexus blockade, whereas the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…Additionally, the authors found a beneficial effect on mood and quality of life. These findings have been corroborated in other studies; one [19] showed higher mean survival rates in the group with greater pain reduction, and another [34] showed an improvement in quality of life in NCPB groups compared to medical management alone. In contrast, other studies have not been able to reproduce similar results [27,31,35].…”
Section: Celiac Plexus Block and Neurolysissupporting
confidence: 76%
See 2 more Smart Citations
“…Additionally, the authors found a beneficial effect on mood and quality of life. These findings have been corroborated in other studies; one [19] showed higher mean survival rates in the group with greater pain reduction, and another [34] showed an improvement in quality of life in NCPB groups compared to medical management alone. In contrast, other studies have not been able to reproduce similar results [27,31,35].…”
Section: Celiac Plexus Block and Neurolysissupporting
confidence: 76%
“…Their results showed that there was no difference in analgesic efficacy with respect to recurrent and residual (celiac or nonceliac) pain between the three, and that neurolytic celiac plexus block gave complete visceral pain relief in 70–80% of patients immediately and in up to 60–75% of patients until death. In contrast, when Suleyman et al [19] compared the transaortic celiac plexus block with splanchnic nerve block in a prospective randomized trial in patients with carcinoma of the body and tail of the pancreas, they found that splanchnicectomy provided greater pain relief and decreased opioid consumption when compared to NCPB. Although there have been only a few published case series and a retrospective study [20-23] regarding use of endoscopic-ultrasonography (EUS) guided CPN since the first report in 1995 [19], a recent review evaluated EUS-guided CPN to be 72.54% effective in pancreatic cancer patients [24].…”
Section: Celiac Plexus Block and Neurolysismentioning
confidence: 95%
See 1 more Smart Citation
“…Splanchnic plexus neurolysis is an effective technique that can potentially improve pain control and quality of life in pancreatic cancer [16]. The efficacy of thoracic splanchnic nerve or celiac ganglion neurolytic blocks have been established for the management of pain in upper gastrointestinal tumors in various studies.…”
Section: Discussionmentioning
confidence: 99%
“…When NCPB was compared with splanchnic nerve neurolytic block (SNB) in 39 patients with head or tail pancreatic cancer it was found that SNB had significantly better impact on pain relief, QOL and analgesic consumption until the end of patients' lives [58]. Another study assessed QOL at 6 months in patients undergoing C-arm guided NCPB compared with splanchnic nerve neurolysis in patients with inoperable upper gastrointestinal tract tumors and with severe uncontrolled pain; the findings showed that splanchnic nerve block had superior results compared with celiac plexus block as more patients had good analgesic response to weak opioids and improvement in the social and cognitive subscales on QOL assessments [59].…”
Section: Neurolysis With Focus On Celiac Neurolysis For Pain Controlmentioning
confidence: 99%